Тhe modern characteristic of the professional improvement of teachers of humanitarian specialities (Pedagogy of Higher and Secondary Education, 2013)
Tsvetkova G. G. Тhe modern characteristic of the professional improvement of teachers of humanitarian specialities.The essential features of self-development of the teachers of humanitarian disciplines are characterized; a comparative analysis of the peculiarities of the professional improvement of the teachers of humanitarian disciplines and the teachers of comprehensive schools is made, the reasons for the success of self-development of teachers of humanitarian disciplines are distinguished in the article. It is proved that the formation of national motives of professional activity of a professional of the high school is a reflexive and changing process of reaching new horizons in the professional activities, assignment of the hierarchy of motives, values, affecting the development of a professional specialist.
Keywords: self-perfection; characteristic features of self-improvement; determined purposeful-motivational orientation; self-reflection; self-denial; through self-restraint; professional self-realization; professional self-regulation